2013
DOI: 10.1371/journal.pone.0065825
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Disturbances in a Temperate Fish Exposed to Sustained High-CO2 Levels

Abstract: As atmospheric CO2 levels rise, the CO2 concentration in ocean surface waters increases through a process commonly referred to as ocean acidification. Recently, surprising behavioural modifications has been detected in the early life stages of tropical coral reef fish exposed to ocean acidification-relevant CO2 concentrations, but it has been unclear if this effect could occur in temperate waters. Here we show several severe behavioural disturbances, including effects on boldness, exploratory behaviour, latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
148
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(155 citation statements)
references
References 30 publications
6
148
1
Order By: Relevance
“…Sensory and cognitive impairment in respect to homing behavior (Munday et al 2009b, Devine et al 2011, prey detection (Cripps et al 2011), predator avoidance , and risk assessment (Ferrari et al 2012) has been observed in coral reef fishes and has been linked to effects of CO 2 on neurotransmitter functions in the brain (Nilsson et al 2012). Behavioral changes including boldness, exploratory behavior, lateralization, and learning were recently also documented in a temperate fish, the three-spined stickleback (Jutfelt et al 2013).…”
Section: Figmentioning
confidence: 99%
“…Sensory and cognitive impairment in respect to homing behavior (Munday et al 2009b, Devine et al 2011, prey detection (Cripps et al 2011), predator avoidance , and risk assessment (Ferrari et al 2012) has been observed in coral reef fishes and has been linked to effects of CO 2 on neurotransmitter functions in the brain (Nilsson et al 2012). Behavioral changes including boldness, exploratory behavior, lateralization, and learning were recently also documented in a temperate fish, the three-spined stickleback (Jutfelt et al 2013).…”
Section: Figmentioning
confidence: 99%
“…By contrast, fish were initially believed to be safe from the effects of OA, as early studies demonstrated a lack of mortality under extremely high CO 2 levels (greater than 10 000 matm) [5]. However, an increasing body of evidence suggests that OA-relevant CO 2 /pH levels induce various sublethal effects in fish, including otolith over-growth [6,7], a shift in behavioural lateralization [8,9], alterations in olfaction that affect detection of cues from substrates, parents [10], prey [11] and predators [8,12,13], and impaired learning [9,14]. Because the gamma-aminobutyric acid type A (GABA A ) receptor antagonist, gabazine, restores proper discrimination of predator odour, learning of predatory cues [14] and behavioural lateralization in OA-exposed fish [8], at least some of the deleterious effects of OA in fish seem to be related to altered neurotransmitter function.…”
Section: Introductionmentioning
confidence: 99%
“…To date, OA research on behaviour has predominantly been investigated in Australian fish that live close to or on coral reefs, a notable exception being a recent study on three-spined stickleback, a temperate fish [9]. Non-reef fish that live near kelp forest ecosystems are candidates to be especially vulnerable because it has recently been demonstrated that upwelling events can significantly affect seawater chemistry [22].…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that projected near-future CO 2 levels can impair sensory systems and alter the behaviour of marine fishes (Munday et al, 2009;Munday et al, 2012;Jutfelt et al, 2013). Behavioural changes include increased boldness and activity Munday et al, 2013;Jutfelt et al, 2013), loss of behavioural lateralization Jutfelt et al, 2013), altered auditory preferences (Simpson et al, 2011) and impaired olfactory function (Munday et al, 2009;Dixson et al, 2010;Ferrari et al, 2011).…”
Section: Introductionmentioning
confidence: 99%